Carbohydrate knowledge, beliefs, and intended practices, of endurance athletes who report exercise-associated gastrointestinal symptoms - Scrivin, Rachel; Costa, Ricardo J. S.; Pelly, Fiona; Lis, Dana; Slater, Gary (Frontiers in Nutrition, 2023)
This study aimed to explore carbohydrate (CHO) knowledge, beliefs, and intended practices of endurance athletes who experience exercise-associated gastrointestinal symptoms (Ex-GIS) compared to those without Ex-GIS. A validated online questionnaire was completed by endurance athletes (n = 201) participating in >60 minutes of exercise that present with Ex-GIS (n = 137) without (n = 64). Descriptive statistics were used for parametric and non-parametric data with appropriate significance tests. Associations between categorical data were assessed by Chi-square analysis, and post-hoc Bonferroni tests were applied when significant. A content analysis of open-ended responses was grouped into themes, and quantitative statistics were applied. Participants included runners (n = 114, 57%), triathletes (n = 43, 21%) and non-running sports (n = 44, 21%) who participate in recreational competitive (n = 74, 37%), recreational non-competitive (n = 64, 32%), or competitive regional, national, or international levels (n = 63, 31%). Athletes correctly categorized CHO (x̄ = 92-95%) and non-CHO (x̄ = 88-90%) food and drink sources. On a Likert scale of 1 (strongly disagree) to 5 (strongly agree) athletes typically agree or strongly agree that consuming CHO around key training sessions and competitions enhances athletic performance [median = 4 (IQR, 4-5)], and they intend to consume more CHO around exercise [median = 3 (IQR, 2-3)]; no differences in beliefs and intentions were found among athletes with or without Ex-GIS. To enhance athletic performance, most endurance athletes intend to consume more CHO around exercise. Adequate knowledge of CHO-containing food sources was apparent; however, specific CHO ingestion practices remain to be verified.